The First Russian Experience of Using Palovarotene for the Treatment of Fibrodysplasia Ossificans Progressiva: Two Case Reports - Irina P. Nikishina; Valeriya G. Matkava; Svetlana V. Arsenyeva; Emil G. Gasymov; Alia N. Arefieva (Педиатрическая фармакология)
Background. Fibrodysplasia ossificans progressiva (FOP) — is an extremely rare genetic disorder with an autosomal dominant type of inheritance. FOP is associated with a genetically determined disorder caused by the presence of a specific mutation in the ACVR1/ALK2 gene encoding the bone morphogenetic protein receptor. FOP is clinically manifested by the unrestrained formation of heterotopic ossifications, leading to a gradual progression of disability up to complete immobility of the patient. At an early age, the disease can be recognized by the presence of characteristic phenotypic stigmas, mainly the characteristic malformation of the thumbs, confirming the diagnosis by molecular genetic analysis. Early diagnosis of FOP avoids unnecessary iatrogenic manipulations and slows down the progression of the disease. Up until recently, there was no therapy that had a pathogenetic effect, preventing the development of ossifications. The first and only drug that has proven its effectiveness as a result of clinical trials and is registered for use in patients with FOP in a number of countries is palovarotene.Case reports: The publication presents the first Russian experience of using palovarotene with a description of two clinical observations of patients with a genetically confirmed diagnosis of FOP. The clinical picture, the difficult path to diagnosis, and the encouraging experience of treating patients, including anti-inflammatory therapy using Janus kinase inhibitors (tofacitinib) and pathogenetic therapy with palovarotene, are described.Conclusion. The aggressive nature of the course of FOP, which inevitably leads to severe disability of patients, necessitates the widespread attention of practitioners to the early diagnosis of FOP, an in-depth study of the factors determining progression, and new opportunities for pathogenetic therapy allow us to count on improving the prognosis of this extremely serious disease.